LIMBIC ENCEPHALITIS OF HERPESVIRUS ETIOLOGY - E. V. Simonova (Detskie Infekcii (Moskva), 2015)
Based on the literature data and our personal observations in the article discusses the types of variants of the course of nervous system caused by herpesviruses. In the description of a clinical case demonstrated a classic example of limbic encephalitis infectious etiology. The study involved 36 children with various neurological and infectious diseases: 19 children with the diagnosis - convulsions, 8 children with the diagnosis — epilepsy, 5 children with acute viral encephalitis, 3 children with neuropathies. It was established that in the genesis of diseases such as epilepsy, convulsive syndrome, limbic encephalitis, neuropathy peripheral nerves leading role belongs to of herpes virus infection, in which the dominant role belongs HHV-6 infection. Pathogenetically proved the impact of the virus on the receptor apparatus of glia with the disorder of the functional state of mitochondria of these cells. According to our own observations provided data that result in persistence of HHV-6 variant-in mono or in combination with other herpesviruses growing threat of epilepsy and other neurological disorders.